Associations between sleep disorder symptoms, self-compassion, and basic psychological needs in Swiss elite athletes - Philipp Röthlin; Stephan Horvath; Gareth Morgan; Daniel Birrer (Bern Open Publishing, 2023)
Introduction Sleep is an important topic in competitive sports, however, there is only limited data from Switzerland in terms of prevalence of sleep disorders in athletes. Many factors may affect sleep, including demographic factors (e.g., age), current stressful events (e.g., injuries), but also factors like basic psychological need satisfaction and frustration as well as self-compassion. It is unclear to what extent all these factors are associated with sleep problems. Methods A representative sample of Swiss athletes (N = 1,003, Mage = 21.69, SDage = 7.09, 54% women, 37% team sports, 10% injured) answered questions about of sleep disorder symptoms, extent of basic need satisfaction and frustration, and self-compassion. Results The prevalence on symptoms of sleep disorders (18%) is comparable to elite sport samples from other countries. A multiple regression was conducted in order to evaluate central factors related to sleep disorder symptoms. Results show that older athletes (β = 0.16, p < .001) and athletes who report need frustration (β = 0.20, p < .001) experience more sleep disorder symptoms, while self-compassionate athletes address less symptoms (β = -.22, p < .001). Need satisfaction, type of sport, gender and injury status were unrelated to sleep disorder symptoms (all βs < 0.04, all ps > .25). In total, all factors explained only 16% of the variance in sleep disorder symptoms. Discussion/Conclusion Interventions that prevent basic need frustration and increase self-compassion may be potential targets for improving sleep quality in athletes. In addition, other factors that are more strongly associated with sleep problems should be considered.